Quantification of Age-Related Decline in Transcriptional Homeostasis. Issue 19 (17th September 2021) - Gupta, Krishan; Yadav, Princey; Maryam, Sidrah; Ahuja, Gaurav; Sengupta, Debarka
Graphical abstract: Highlights: Aging features breakage of RNA homeostasis. We propose a score to measure the balance between spliced and unspliced RNA from scRNA-Seq data. We report a set of genes undergoing homeostatic breakdown during pancreatic aging. Analysis suggests the existence of transcripitional restoration as a potential anti-aging mechanism. Abstract: Age-dependent dysregulation of transcription regulatory machinery triggers modulations in the gene expression levels leading to the decline in cellular fitness. Tracking of these transcripts along the temporal axis in multiple species revealed a spectrum of evolutionarily conserved pathways, such as electron transport chain, translation regulation, DNA repair, etc. Recent shreds of evidence suggest that aging deteriorates the transcription machinery itself, indicating the hidden complexity of the aging transcriptomes. This reinforces the need for devising novel computational methods to view aging through the lens of transcriptomics. Here, we present Homeostatic Divergence Score (HDS) to quantify the extent of messenger RNA (mRNA) homeostasis by assessing the balance between spliced and unspliced mRNA repertoire in single cells. We validated its utility in two independent aging datasets, and identified sets of genes undergoing age-related breakdown of transcriptional homeostasis. Moreover, testing of our method on a subpopulation of human embryonic stem cells revealed a set of differentially processed transcripts segregating these subpopulations. Our preliminary analyses in this direction suggest that mRNA processing level information offered by single-cell RNA sequencing (scRNA-seq) data is a superior determinant of chronological age as compared to transcriptional noise.